2009
DOI: 10.1007/s11468-009-9111-5
|View full text |Cite
|
Sign up to set email alerts
|

Real-time Detection of Single Immobilized Nanoparticles by Surface Plasmon Resonance Imaging

Abstract: In this manuscript, a new approach in surface plasmon resonance microscopy is presented. The method provides optical real-time detection of single nanoparticles on surfaces. The potential of the method is demonstrated recording spherical dielectric particles as small as 40 nm in diameter and single HIV virus-like particles having diameters of ∼100 nm both immobilized on functionalized surfaces. The surface plasmon resonance signal in the binding spots was found to be almost linearly proportional to the size of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
79
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(88 citation statements)
references
References 25 publications
5
79
0
4
Order By: Relevance
“…Only recent groundbreaking studies performed in independent working groups helped in realizing the potential of SPR-based sensors in studies of biological submicrometer and nanoparticles [4][5][6][7]. Zybin and colleagues used SPR-based ''microscopy'' (also called ''SPR nanoscopy'') to detect the binding of individual polystyrene particles of different sizes (minimal used size was 40 nm diameter) to the functionalized sensor surface [6].…”
Section: Introductionmentioning
confidence: 99%
“…Only recent groundbreaking studies performed in independent working groups helped in realizing the potential of SPR-based sensors in studies of biological submicrometer and nanoparticles [4][5][6][7]. Zybin and colleagues used SPR-based ''microscopy'' (also called ''SPR nanoscopy'') to detect the binding of individual polystyrene particles of different sizes (minimal used size was 40 nm diameter) to the functionalized sensor surface [6].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the deviation to the N (0, 1)-curve gets smaller with increasing α for all considered procedures. The scale estimatorŜ (4) used for the Hodges-Lehmann based procedures, seems to result in a somewhat smaller difference to the N (0, 1)-curve. In the investigated situations, the randomization principle can lead to approximately distribution-free procedures, but this is not guaranteed.…”
Section: Arl 0 -Curves Under Different Distributionsmentioning
confidence: 97%
“…If the coordinate is part of a virus adhesion, it has a sudden positive or negative jump depending on whether the coordinate belongs to the bright spot or the dark circle. More details on the sensor can be found in [4] or [5]. Figure 1(b) shows a time series from a PAMONO data set.…”
Section: Introductionmentioning
confidence: 99%
“…However, prism-based systems can be physically bulky and limited in their spatial resolution, and their long working distance can produce image distortion [126,127]. To address these issues, Zare et al first demonstrated SPR imaging using a high numerical aperture objective, as shown in Figure 5a [128].…”
Section: Surface Plasmon Resonance Imaging Microscopymentioning
confidence: 99%